ANALISIS PROKSIMAT DAN ORGANOLEPTIK COOKIES SUBSTITUSI DAGING IKAN TERI BERBAHAN BAKU TEPUNG KELADI (Xanthosoma sagittifolium) PERENDAMAN DAN TEPUNG KELADI TERMODIFIKASI ( - Pitunani, Maulid Wati (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
To improve the quality of Xanthosoma sagittifolium flour were modified by fermentation using locally lactic acid bacteria fermented cassava in processing wikau maombo. As a comparison was carried out the immersion of Xanthosoma sagittifolium tuber which produce immersion flour. Each of flour produced was performed physicochemical test (swelling power, solubility and pH) and analysis of protein content of the raw material. To complete the nutritional of the protein cookies then made substitution with teri fish. The purposes of this study were to determine the formulation and nutritional value of cookies products substitute with anchovies using two different raw materials (immersion and modification of the taro flour). This research method used a completely randomized design with 4 treatments and 4 replicates in order to obtain 16 experimental units.The treatments that had been done were the addition of taro flour immersion and the addition of taro flour modification. Both of each flour substituted with teri fish, in order to obtain two types of cookies. Based on the organoleptic results, obtained treatment M1 (modification flour of 70%: teri fish 10%: wheat flour 20%) and K1 (immersion flour 70%: teri fish 10%: wheat flour 20%) as a product of cookies selection of panelists. Moisture, protein, fat, ash and glucose of M1products are 8.7% 17.0% 48.0% 2.6% and 9.0%, respectively while for the product K1 are 8.5% 15.0% 40, 7% 2.0% and 8.7%, respectively